Effect of Hand Hygiene Intervention on The Absenteeism of Pre-School Children in Klang Valley, Malaysia: A Quasi-experimental Study - Nurul Azmawati Mohamed; Mohd Dzulkhairi Mohd Rani; Tengku Zetty Maztura Tengku Jamaluddin; Shalinawati Ramli; Habibah Faroque; Farisha Nur Abd Samad; Abdul Rashid Arifen; Aisyah Ar Redha Che Amir Farid; Ilina Isahak; Zarini Ismail (Springer, 2024)
Indexed by SCOPUS/ERA